The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.18510/hssr.2020.8519
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Perceived Organizational Support and Self-Efficacy to Change Readiness for Change in Hospital of Muhammadiyah Malang University, Indonesia

Abstract: readiness to change in the Hospital of Muhammadiyah Malang University. Methodology: This research sample of 129 respondents, taken based on Purposive Sampling of Muhamadiyah University Hospital’s employee population. This path analysis technique will be used in testing the amount of contribution shown by the path coefficient on each path diagram of the causal relationship between variables X1, X2, and X3 on Y. Main Findings: Self-efficacy and perceived organizational support have a positive and sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…This study found that teachers considered changing the learning system as a response to situations such as when there was Covid19, which was the right step. Teachers believe that changes in digital-based learning systems have a good impact on learning (Mardhatillah & Rahman, 2020;Riyanto et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…This study found that teachers considered changing the learning system as a response to situations such as when there was Covid19, which was the right step. Teachers believe that changes in digital-based learning systems have a good impact on learning (Mardhatillah & Rahman, 2020;Riyanto et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The organization's educational initiatives are deeply rooted in Islamic values and principles, aiming to instill these values in students while providing quality education. Furthermore, Muhammadiyah's involvement in healthcare is evident through the ownership and management of hospitals, reflecting its commitment to providing medical services aligned with Islamic principles [2,21,24,25]. The organization's hospitals serve as essential healthcare facilities, contributing to the well-being of the community while upholding Islamic values in the provision of medical care.…”
Section: Muhammadiyah As Islamic Organization and Relation To Muhamma...mentioning
confidence: 99%